Kualitas Pelayanan Kesehatan Puskesmas (Suatu Studi Kasus Pelayanan Kesehatan di Puskesmas Blado, Kabupaten Batang, Jawa Tengah).Quality Health Service in Puskesmas (A Case Study on Health Service in Puskesmas Blado, Bat - Perpustakaan UGM, i-lib ([Yogyakarta] : Sekolah Pascasarjana Universitas Gadjah Mada, 2003)
ABSTRACTThis research aims to describe public health service in Puskesmas Blado and to analysis the influence of organization orientation, organization climate and resources to quality public health service in Puskesmas Blado.This research uses qualitative descriptive method with interactive analysis model. Unit of analysis in this research is Puskesmas Organization. Respondent or key information consists of Puskesmas officer (Doctors/ chief of Puskesmas, nurses, and administration staff) and people who get Puskesmas Blado service (21 people).The result of this research indicates public health service in Puskesmas Blado has been influenced by organization climate, bureaucracy orientation, and resources variables. Public services quality in Puskemas Blado is still in low conditions. This is because relationships between doctors/ Puskesmas officer with patients in bad conditions. Low quality of public health service in Puskesmas Blado influenced by 1) bad organization climate, where decision making practice, communication flows, and conditions to create work situation for officer satisfaction are still in low level, 2) bureaucracy orientation is still directed to power orientation than public services orientation, and 3) limited resources in quantity and quality of human power, limited and less functional work tools, and limited fund.This research gives several recommendations 1) need to develop conducive organization climate with leadership must have capability to democratic decision, relationship among officers using good dialog communications flows.